Pengaruh Minat Baca Peserta Didik terhadap Pemahaman Kritis Materi Sosiohistoris Arab pra Islam - Nurfadhilah, Nurfadhilah; Erman, Erman; Hasnah, Radhiatul (ISLAMIKA, 2025)
It is motivated by the lack of awareness of students to take advantage of free time to read and the level of analysis related to learning materials that have not been critical. The purpose of this study was to determine the level of students' interest in reading and its effect on students' critical understanding of Sociohistorical material. This research uses a quantitative approach with a correlational method. Based on this research from the analysis using SPSS 25, it is known that the coefficient of determination is 0.23. This means that reading interest can affect critical thinking understanding by 23%, while 77% can be influenced by other variables not examined in this study. Based on this research, it can be concluded that reading interest is influential in generating and improving students' critical thinking.